Pengembangan LKPD Berbasis Pobica (Puzzle Operasi Hitung Bilangan Cacah) Kelas V SDN 010 Samarinda Seberang - Rahmawati, Widya; Sukriadi, Sukriadi; Arafah, Andi Asrafiani; Muhlis, Muhlis; Septika, Hety Diana; Haerani, Rosita Putri Rahmi (FONDATIA, 2025)
This research is motivated by the lack of variation in the use of teaching materials and the need for the development of teaching materials in the form of LKPD integrated with educational game media that can increase student activity in the learning process. This study aims to determine the development process, determine the level of validity, and practicality of LKPD based on Pobica learning media for grade V elementary schools. This research method uses Research and Development (R&D) research with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. Data collection techniques used in this study are interview techniques, observations, and questionnaires in the form of student needs analysis, product validation tests, student responses, and teacher responses. The results of the study are to produce a product in the form of LKPD based on Pobica. The percentage of validity obtained from material experts obtained a percentage of 85% with the category very valid. The percentage of validity obtained from media experts was 87% with the category very valid. The percentage of validity obtained from language experts was 95% with the category "very valid". Practicality assessment is obtained from student responses and teacher responses. In a small-scale trial, the student response questionnaire obtained a percentage of 84% with the category very practical. While in a large-scale trial, a percentage of 79% was obtained with the category practical. The results of the teacher response questionnaire obtained a percentage of 95% with the category very practical.